PENGARUH PEMBERIAN MAKANAN TAMBAHAN PEMULIHAN (PMT-P) TERHADAP STATUS GIZI BALITA GIZI BURUK DI DINAS KESEHATAN KOTA SEMARANG TAHUN 2012 - Fitriyanti, Farida; Mulyati, Tatik (Journal of Nutrition College, 2012)
ABSTRACTBackground : Severe malnutrition is often happened in children under five. It is the most serious stage from process of malnutrition, especially energy and protein. Those do not appropriate with requirement and happen for a long time. Malnutrition is showed by weight and height where those  have linear relation. And those are showed with z-score value by weight-for-height and weight-for-age. An effort to overcome malnutrition is Supplementary Feeding Program of Recovery (PMT-P) where its nutritional value has been measured. So that requirement can be achieved.Method : This study was included on community nutrition with observational research and cohort approach. Subjects were 22 malnourished children under five including on inclusion criteria in Department of Health in Semarang during 60 days (2months). PMT-P was given on formula and biscuit form. It has nutritional value which can contribute 70% of energy requirement and 80% of protein requirement in one day.Result : There was different nutritional status before and after gving PMT-P based on weight-for-height and weight-for-age with p=0.000 and p=0.002. Difference of nutritional status based on weight-for-height happening after PMT-P was from 100% of very thin to 18.2% normal; 40.9% thin; and 40.9% very thin. Whereas it based on weight-for-age was from 86.4% severe malnutrition to 40.9% mild malnutrition. PMT-P also gived contribution of energy of 54.60±15.42% and protein of 79.17±37.75% from daily need.Conclusion : PMT-P for 2 months gives effect for changing of nutritional status based on weight-for-height and weight-for-age of malnourished children under five. It gives contribution of energy of 54.60±15.42% and protein of 79.17±37.75%.Keywords : PMT-Pecovery, severe malnutrition, formula WHO F100